Mediated Intimacies: State Intervention and Gender Violence in Nicaragua - Miklos, Alicia Zoe (Encuentro, 2015)
This article forms part of an inquiry about the reach of legislative changes initiated by Law 779 in Nicaragua, the “Integral Law against Violence towards Women”, passed in February 2012. The primary texts I analyze include the legislative debates for the drafting of Law 779, the body of Law 779, the Reform to the law in October 2013, and the Regulations to Law 779, issued through a presidential proclamation in July 2014. I organize my discussion around the most controversial juridical figure in Law 779: that of mediation. Analyzing the trajectory of Law 779 within the Post-war cultural scene in Nicaragua, I conclude that the reinstatement of mediation represents a regressive reaffirmation of patriarchal authority in the guise of community empowerment. The family centered rhetoric of the Regulation to Law 779 signifies capitulation to the most conservative, religious sectors of society and a dramatic reversal of feminist gains towards recognizing women as subjects with rights. These are in fact battles over the cultural interpretation of women’s place, their autonomy, and the troubled reality of the nuclear family and normative social bonds in twenty-first century Central America. They show that women’s autonomy continues to be symbolically coded as dangerous, even as a threat to the collective interests of the family and the nation.